Influence of charge density and oxygen concentration on combustion paths, thermal efficiency and emissions in a heavy-duty diesel engine. (December 2020) - Lu, Yingying; Pei, Yiqiang; Wu, Binyang; Liu, Yize
Experiments and simulations were conducted to study effects of charge density, temperature, and oxygen concentration on the mixing-controlled engine combustion pathway in heavy-duty diesel engines. Due to the inherent heterogeneity of diesel combustion in high-load operations, the rich and lean mixtures are simultaneous present. The mass and accompanying heat transfers were found to be decisive in determining the combustion path. The chemical transformation from a richer mixture to a leaner mixture is primarily driven by charge density, which activates the combustion process, and reduction in oxygen concentration, which stagnates the mass and heat transfer and chemical transformation, reduces the reactivity of the mixtures. The difference in mass and heat transfer processes causes differences in the mass fractions of mixtures with different equivalence ratio intervals. The different mixtures produce different mass fractions of intermediate combustion products (carbon dioxide, CO), different heat releases, and different mass temperature distributions. It is found that the accumulated CO correlates well with the gross indicated thermal efficiency and soot emission; the mass averaged temperature and the high temperature abidance scale (HTAS) correlate well with NOx emissions. A significant optimization of the overall engine performance could be achieved by simultaneously minimizing the HTAS and accumulated CO.